Making sense of the labour movement as we confront the burden of the future - Marks, Monique (New Agenda: South African Journal of Social and Economic Policy, 2024)
Professor MONIQUE MARKS presents a unique take on the new challenges and opportunities facing the labour movement in South Africa today. In a speech she gave at the 1973 Durban Strikes 50th Remembrance last year to celebrate the significance and the gains of the ‘Durban Moment,’1 she emphasised the need to provide hope and a sense of belonging to those currently relegated to the margins of society.